Functional stoichiometry of the unitary calcium-release-activated calcium channel - Ji, Wei; Xu, Pingyong; Li, Zhengzheng; Lu, Jingze; Liu, Lin; Zhan, Yi; Chen, Yu; Hille, Bertil; Xu, Tao; Chen, Liangyi (Proceedings of the National Academy of Sciences - PNAS, 2008)
Two proteins, STIM1 in the endoplasmic reticulum and Orai1 in the plasma membrane, are required for the activation of Ca(2+) release-activated Ca(2+) (CRAC) channels at the cell surface. How these proteins interact to assemble functional CRAC channels has remained uncertain. Here, we determine how many Orai1 and STIM1 molecules are required to form a functional CRAC channel. We engineered several genetically expressed fluorescent Orai1 tandem multimers and a fluorescent, constitutively active STIM1 mutant. The tandem multimers assembled into CRAC channels, as seen by rectifying inward currents and by cytoplasmic calcium elevations. CRAC channels were visualized as fluorescent puncta in total internal reflection microscopy. With single-molecule imaging techniques, it was possible to observe photo-bleaching of individual fluorophores and to count the steps of bleaching as a measure of the stoichiometry of each CRAC channel complex. We conclude that the subunit stoichiometry in an active CRAC channel is four Orai1 molecules and two STIM1 molecules. Fluorescence resonance energy transfer experiments also showed that four Orai1 subunits form the assembled channel. From the fluorescence intensity of single fluorophores, we could estimate that our transfected HEK293 cells had almost 400,000 CRAC channels and that, when intracellular Ca(2+) stores were depleted, the channels clustered in aggregates containing approximately 1,300 channels, amplifying the local Ca(2+) entry.